Analisis Sikap Siswa terhadap Keberagaman Suku di Kelas VIII SMP Swasta Utama Medan - Anggi Putri Simamora; Desi Mertina Br Sembiring; Dewi Pratiwi; Mutia Haryani Siregar; Putri Delvia; Raudatul Fadilla; Sania Siregar; Ika Purnamasari (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
At the junior high school level (SMP), students begin to recognize the importance of values ​​of togetherness in diversity. However, this understanding does not always run smoothly because of cultural and background differences that can affect the way students interact with each other. This study uses a descriptive approach. The purpose of this study is to analyze students' attitudes towards ethnic diversity in class VIII of a private junior high school. Data collected through questionnaires will be analyzed to obtain an overview of students' attitudes towards diversity related to the topic and objectives of the research applied. The results of the study showed that there were no significant differences in attitudes between students with different ethnic backgrounds. This means that positive attitudes towards ethnic diversity are evenly distributed among various ethnic backgrounds, indicating that ethnic factors are not a barrier to social interaction in the classroom, where most students have similar views on the importance of respecting differences and working together with friends from different ethnic groups.